Implementasi Tes Koneksi Jaringan Internet Pada Server Linux Ubuntu Dari Luar Jaringan Menggunakan Remote Akses Putty (Studi Kasus : Uptd Rsud Asih Husada Langensari) - Fariazis, Ida; Purnomo, Joko; Purbasari, Wika (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2025)
In line with the development of the digital era which is increasingly advanced and developing network access is required to provide safe and reliable security for both organizations, business entities or government agencies, all need access control and monitoring from owners and managers. The need for access, especially access from outside the office network is very necessary. One of them is by implementing an internet network connection test on the Linux Ubuntu server from outside the network using remote putty access. This research aims to be able to help users monitor connections from outside the network effectively and efficiently because users do not need to come to the location to check network connections directly. The methods used in this research are identification of user needs, identification of the current system, and system development methods using the Network Development Life Cycle (NDLC) including analysis, design, simulation, implementation (application), monitoring (testing), and management. The resulting network development system is a remote access system from outside the network using the putty application implemented on the server at UPTD RSUD Asih Husada Langensari, so that it can be run on other computer devices without having to come to the location directly.